2013
DOI: 10.1111/ajco.12052
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of Rac1, Pak1 and Rock1 in gastric carcinoma

Abstract: AimsRac1, Pak1 and Rock1 are indicators related to gastric cancer invasion and metastasis, but few reports discuss all three kinds of protein in research on gastric cancer invasion and metastasis. The aim of this study was to investigate the expression and clinical significance of Rac1, Pak1 and Rock1 in gastric carcinoma.MethodsRac1, Pak1 and Rock1 expression in 158 cases of gastric carcinoma were investigated via immunohistochemical staining and clinical analysis.ResultsThe positive expression rates of Rac1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
(36 reference statements)
2
19
0
1
Order By: Relevance
“…Our studies discovered that high Rac1 levels were well correlated with gastric cancer malignancy and predicted poor survival in gastric cancer patients as assessed in clinical specimens. Our findings are consistent with previous studies which suggested a correlation of Rac1 with gastric cancer malignancy (20,21). We also found that Rac1 was highly expressed in intestinal-type gastric cancer and positively correlated with tumor differentiation, local invasion and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our studies discovered that high Rac1 levels were well correlated with gastric cancer malignancy and predicted poor survival in gastric cancer patients as assessed in clinical specimens. Our findings are consistent with previous studies which suggested a correlation of Rac1 with gastric cancer malignancy (20,21). We also found that Rac1 was highly expressed in intestinal-type gastric cancer and positively correlated with tumor differentiation, local invasion and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Rac1 regulates a diverse spectrum of cellular functions including tumorigenesis (11), angiogenesis (12,13) and metastasis (11,14,15). Overexpression of Rac1 occurs in several different types of tumors including breast (16,17), colon (18), bladder (19), and gastric cancer (20,21). Rac1 overexpression was observed in metastatic gastric (21), breast (15), prostate (22), bladder upper urinary tract cancer (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROCK1 is a target of several miRNAs in various cancers including miRNA-584 in renal cell carcinoma [39], miRNA-335 in neuroblastoma [40], and miRNA146a in prostate cancer [41]. In gastric cancer, ROCK1 has been positively correlated with LN metastasis and TNM stage [42], and is involved in miRNA-148a-induced suppression of gastric cancer cell migration and invasion [30]. Further, ROCK1 inhibitor promoted apoptosis in gastric cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…According to the in silico analyses, we predicted Rac1 as a direct target, which encodes a small G-protein that is an important member of the Rho family (20). Rac1 is overexpressed in various types of cancer including breast, colon and lung carcinomas (21)(22)(23) and partici pates in all stages of tumor formation (24).…”
Section: Discussionmentioning
confidence: 99%